2022
DOI: 10.1186/s12871-022-01764-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bilateral paravertebral nerve block on cognitive function in elderly patients undergoing radical gastrectomy for gastric cancer: a prospective randomized double-blind controlled trial

Abstract: Objective To investigate the effect of a bilateral paravertebral block (PVB) on cognitive function in elderly patients undergoing radical gastrectomy for gastric cancer. Methods Sixty patients (40 men and 20 women) aged 65–80 undergoing radical gastrectomy surgery under general anaesthesia were included and randomly assigned to either the PVB group or the control group. Patients in the PVB group had before incision a single-shot ultrasound-guided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Table 1 includes details about the RCTs, among them six RCTs ( Xie et al, 2019 ; Wei et al, 2020 , 2022 ; Chen et al, 2022 ; Heng et al, 2022 ; Dongjie et al, 2023 ) enrolled patients who underwent thoracoscopic surgery, one ( Jin L. et al, 2020 ) enrolled patients who underwent esophagectomy, one ( Shang et al, 2022 ) enrolled patients who underwent gastrectomy, and one ( Strike et al, 2019 ) enrolled patients who underwent Transapical Aortic Valve Replacement. Five RCTs compared the incidence of POD between PVB and non-PVB groups ( Strike et al, 2019 ; Jin L. et al, 2020 ; Heng et al, 2022 ; Wei et al, 2022 ; Dongjie et al, 2023 ), while other five RCTs, compared the incidence of DNR ( Xie et al, 2019 ; Wei et al, 2020 ; Chen et al, 2022 ; Heng et al, 2022 ; Shang et al, 2022 ). Only one study ( Chen et al, 2022 ) reported the incidence of POCD ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 includes details about the RCTs, among them six RCTs ( Xie et al, 2019 ; Wei et al, 2020 , 2022 ; Chen et al, 2022 ; Heng et al, 2022 ; Dongjie et al, 2023 ) enrolled patients who underwent thoracoscopic surgery, one ( Jin L. et al, 2020 ) enrolled patients who underwent esophagectomy, one ( Shang et al, 2022 ) enrolled patients who underwent gastrectomy, and one ( Strike et al, 2019 ) enrolled patients who underwent Transapical Aortic Valve Replacement. Five RCTs compared the incidence of POD between PVB and non-PVB groups ( Strike et al, 2019 ; Jin L. et al, 2020 ; Heng et al, 2022 ; Wei et al, 2022 ; Dongjie et al, 2023 ), while other five RCTs, compared the incidence of DNR ( Xie et al, 2019 ; Wei et al, 2020 ; Chen et al, 2022 ; Heng et al, 2022 ; Shang et al, 2022 ). Only one study ( Chen et al, 2022 ) reported the incidence of POCD ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study ( Chen et al, 2022 ) reported the incidence of POCD ( Table 2 ). Among the RCTs, five ( Strike et al, 2019 ; Jin L. et al, 2020 ; Wei et al, 2020 ; Heng et al, 2022 ) used continuous paravertebral analgesia post-operation, and four used the same intravenous analgesia PCA settings between PVB and non-PVB groups ( Xie et al, 2019 ; Chen et al, 2022 ; Shang et al, 2022 ; Dongjie et al, 2023 ). It’s worth noting that, except one study Chen et al, all participants elderly.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16] Recent years have seen the development of multimodal analgesia using nerve blocks as the primary mode of perioperative analgesia, which has been shown to effectively provide analgesia to promote early perioperative recovery. [17][18] Some studies have proposed an US-guided technique called "subcostal" TAPB for producing reliable analgesia for supraumbilical abdominal surgery, [13] and minimizing the perioperative stress response. [19] However, TAPB provides only somatic (i.e., abdominal wall) analgesia and not visceral analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…POCD is one of the most common complications in patients who have undergone laparoscopic gastric cancer surgery and is related to many factors, such as age, underlying disease, surgical and anesthesia methods, and surgical time. Anesthetic drugs can act on multiple targets in the brain, thereby affecting brain function, and the choice of drug is an important factor leading to postoperative POCD in patients[ 14 ]. MMSE is a commonly used scale for evaluating cognitive function in clinical practice.…”
Section: Discussionmentioning
confidence: 99%